2006
DOI: 10.1016/j.marpolbul.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Are Taxonomic Distinctness measures compliant to other ecological indicators in assessing ecological status?

Abstract: Assessing the ecological status, a concept implemented in the European Water Framework Directive [EC, 2000. Directive of the European Parliament and of the Council 2000/60/EC establishing a framework for community action in the field of water policy PE-CONS 3639/1/00, p. 72], requires the application of methods capable of distinguishing different levels of ecological quality. The Average Taxonomic Distinctness has been used as tool in this context, and we tested the robustness of Taxonomic Distinctness measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…Thus, in spite of the fact that richness and rarity show different patterns across the four habitats (which suggests that the information provided by them are complementary), both show a clear tendency to decrease under perturbation. Similarly, Salas et al. (2006) found that taxonomic distinctness measures of marine benthic communities were less sensitive than other diversity measures to the effects of eutrophication in coastal lagoons.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in spite of the fact that richness and rarity show different patterns across the four habitats (which suggests that the information provided by them are complementary), both show a clear tendency to decrease under perturbation. Similarly, Salas et al. (2006) found that taxonomic distinctness measures of marine benthic communities were less sensitive than other diversity measures to the effects of eutrophication in coastal lagoons.…”
Section: Discussionmentioning
confidence: 93%
“…TD was calculated as the mean taxonomic distance between all pairs of taxa, while TTD is a modification of species richness that incorporates family interrelatedness explicitly (Salas et al . ). We investigated the potential of established metrics of aquatic disturbance as indicators of WLF in lakes by focusing on two common metrics that have been shown to respond to a range of different pressures in both rivers and lakes (Wallace, Grubaugh & Whiles ; Sandin & Johnson ; Schmidt‐Kloiber et al .…”
Section: Methodsmentioning
confidence: 97%
“…The importance of WLF for phylogenetic and taxonomic richness of algal and invertebrate assemblages was examined by quantifying each of their total phylogenetic diversity (PD), taxonomic distinctness (TD) and total taxonomic distinctness (TTD) using PRIMER ® 6.1.8. Phylogenetic diversity was calculated as the sum of the phylogenetic branch lengths among species (Faith, ), TD was calculated as the mean taxonomic distance between all pairs of taxa, while TTD is a modification of species richness that incorporates family inter‐relatedness explicitly (Clarke & Warwick, ; Salas et al ., ). Hierarchical Linnaean classification served as a proxy for cladograms and a basis for measuring relatedness.…”
Section: Methodsmentioning
confidence: 99%